2017
DOI: 10.1016/j.eucr.2017.03.020
|View full text |Cite
|
Sign up to set email alerts
|

The Case of Huge Pure Lipoma of the Spermatic Cord Misdiagnosed as Inguinal Hernia

Abstract: Clinically, pure spermatic-cord lipoma has not been recognized as a disease entity but regarded as an incidental finding at the time of hernia repair, because it presents groin symptoms and clinical findings indistinguishable from those of inguinal hernia. We report the successful treatment of case of huge pure spermatic-cord lipoma originally misdiagnosed as inguinal hernia. The patients had tumor excision without orchiectomy. Symptoms improved without any complication. In patients with inguinal hernia sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 7 publications
0
11
0
2
Order By: Relevance
“…Sonography is sufficient to evaluate a scrotal mass and differentiate a testicular mass from a scrotal lipoma. 11 We found that the mass did not show any connection to the peritoneal cavity and therefore we could exclude an inguinal hernia. However, sonography alone is insufficient to diagnose a giant spermatic cord lipoma.…”
Section: Case Reportmentioning
confidence: 75%
“…Sonography is sufficient to evaluate a scrotal mass and differentiate a testicular mass from a scrotal lipoma. 11 We found that the mass did not show any connection to the peritoneal cavity and therefore we could exclude an inguinal hernia. However, sonography alone is insufficient to diagnose a giant spermatic cord lipoma.…”
Section: Case Reportmentioning
confidence: 75%
“…While ultrasonographic evaluation is typically effective at differentiating testicular carcinoma from lipoma, unclear sonographic findings and a high symptomatic suspicion of lipoma (i.e. slowly growing, non-reducible, fixed, relatively hard, nontender mass) should prompt further preoperative modalities of investigation such as CT or MRI for diagnostic confirmation [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spermatic-cord lipomas are usually detected incidentally during the hernia repair surgery. Therefore, Jo et al advised to perform an abdominopelvic CT and MRI in patients with a slowly growing, non-reducible, fixed, relatively hard and non-tender mass [3]. Moreover, an encysted spermatic cord hydrocele was described in a male patient as a painful, well circumscribed, 4 cm sized swelling in the left inguinal region which clinically mimicked an incarcerated inguinal hernia [4].…”
Section: Discussionmentioning
confidence: 99%